Analisis Rasio Efisiensi, dan Kemandirian Keuangan Daerah Untuk Menilai Kinerja Keuangan Daerah Pemerintah Kabupaten Soppeng - Syamsurizal Syamsurizal,; Chalid Imran Musa ,; Nurman Nurman ,; Muh. Ichwan Musa ,; Andi Mustika Amin , (Jurnal Manajemen Riset Inovasi, 2023)
This research aims to determine the level of efficiency and level of financial independence of the Soppeng Regency government in financing its government activities. The type of data used in this research is quantitative data obtained from direct observation and documentation studies of financial reports relating to the realization of regional expenditure. The data is analyzed using the quantitative descriptive analysis method, namely by carrying out calculations on the financial data obtained. The results of this research show that the average value of the Soppeng Regency government's efficiency level from 2018 to 2022 shows that the efficiency ratio is inefficient because it is above 100 percent, which indicates that the regional government is inefficient. At the level of independence, the Soppeng Regency regional government is still in the category of instructive relationship patterns. This means that the regional government is not yet independent in financing its government activities and the role of the central government is still very dominant, which indicates that the level of dependence of the Soppeng Regency government is still high on the central government